2017
DOI: 10.1038/nature24675
|View full text |Cite|
|
Sign up to set email alerts
|

Pluripotent state transitions coordinate morphogenesis in mouse and human embryos

Abstract: The foundations of mammalian development lie in a cluster of embryonic epiblast stem cells that, in response to extracellular matrix signalling, undergo epithelialization creating an apical surface in contact with a cavity1,2, a fundamental event for all subsequent development. Concomitantly, epiblast cells transit through distinct pluripotent states3,4, before lineage commitment at gastrulation. These pluripotent states have been characterized at the molecular level5, but their biological importance remains u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
217
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(240 citation statements)
references
References 45 publications
21
217
2
Order By: Relevance
“…GO analysis revealed significant enrichment of regulators of cell adhesion, which is critical for cell polarization (Ebnet et al , ) that initiates lumenogenesis after exit from naïve pluripotency (Shahbazi et al , ). To test whether Zfp281 controls polarization, we generated spheroids in Matrigel as described before (Shahbazi et al , ). WT ESCs formed polarized spheroids with expanded lumens that were encircled by apical F‐actin, while Zfp281 KO cells grew as unpolarized and disorganized cellular aggregates that were morphologically similar to ESCs (Fig D).…”
Section: Resultsmentioning
confidence: 99%
“…GO analysis revealed significant enrichment of regulators of cell adhesion, which is critical for cell polarization (Ebnet et al , ) that initiates lumenogenesis after exit from naïve pluripotency (Shahbazi et al , ). To test whether Zfp281 controls polarization, we generated spheroids in Matrigel as described before (Shahbazi et al , ). WT ESCs formed polarized spheroids with expanded lumens that were encircled by apical F‐actin, while Zfp281 KO cells grew as unpolarized and disorganized cellular aggregates that were morphologically similar to ESCs (Fig D).…”
Section: Resultsmentioning
confidence: 99%
“…These improvements will further increase the placental volume of the embryo during post‐implantation . Under 3D in vitro culture conditions, ESCs with self‐assembling properties can develop into natural embryos‐like structures . For example, Harrison et al found that in 3D matrigel, after 96 hours, ESCs can self‐assemble into a cylindrical structure similar to a natural mouse embryo (Figure D).…”
Section: Bioengineered Microenvironment For Early Embryo Culture In Vmentioning
confidence: 99%
“…58 Under 3D in vitro culture conditions, ESCs with self-assembling properties can develop into natural embryos-like structures. 18,34,42,62,63 For example, Harrison et al 41 found that in 3D matrigel, after 96 hours, ESCs can self-assemble into a cylindrical structure similar to a natural mouse embryo ( Figure 3D). The discovery provides a powerful platform for studying the physical and molecular mechanisms of embryonic development.…”
Section: Static Culture Platformsmentioning
confidence: 99%
“…As mouse and human embryos implant into the uterus, the amniotic cavity (which will hold the developing fetus) begins to form. Shahbazi et al 1 provide in vitro evidence that, before implantation, naive pluripotent cells (which can give rise to all bodily cell lineages) place their apical edges in contact to form a polarized 'rosette' structure. The secreted protein leukaemia inhibitory factor (LIF) promotes expression of pluripotency genes in naive pluripotent cells, and these genes, in turn, inhibit the production of sialomucins -negatively charged proteins needed for amniotic-cavity formation.…”
Section: Early Embryos Kept In Checkmentioning
confidence: 99%
“…One way is to implement checkpoints, similar to those in place during the cell cycle, to block progression until specific criteria are met. In a paper online in Nature, Shahbazi et al 1 report just such a checkpoint during early development in mammals.…”
mentioning
confidence: 99%